The Impact of Customer Value, Price, Brand Image and Service Quality on Customer Satisfaction on XL Prepaid Card 4G Network in Bekasi City - Triandewo, Maris Agung; Dewantoro, Willy (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2021)
This study has intention to identify the impact of Customer Value, Price, Brand Image and Service Quality on Customer Satisfaction on the 4G XL Prepaid Card Network in Bekasi City. The design of this research is descriptive and causality. Purposive sampling was used with 115 respondents. The analysis method uses multiple regression and processed with IBM Statistic 20. From this research it can be concluded that from all dependent variables only Price that has no impact on Customer Satisfaction.